The Concept of Educational Evaluation in Islamic Perspective - Umi Septina Anggraheni; Abid Nurhuda; Syukron Ni’am; Siti Jaroyatun Ni’mah (Nusantara Education, 2023)
Evaluation is a fundamental instrument for measuring the achievement of goals in any organized activity, particularly in education. Within the Islamic tradition, evaluation occupies a central position, as reflected in the practices of the Prophet Muhammad in guiding, assessing, and refining the understanding and conduct of his companions. This study aims to explore and articulate the concept of educational evaluation from an Islamic perspective, emphasizing its philosophical foundations and practical implications. This research adopts a qualitative design using a literature study approach. Data were collected through documentation of classical Islamic texts, prophetic traditions, and contemporary scholarly works on Islamic education. The analysis was conducted using content analysis to identify key themes, principles, and frameworks related to evaluation. This method allows for a systematic and in-depth interpretation of normative sources and their relevance to modern educational contexts. The findings indicate that educational evaluation in Islam is inherently comprehensive and integrative, encompassing cognitive (knowledge), affective (attitudes), and psychomotor (skills) dimensions. These aspects are not treated in isolation but are viewed as interconnected components of holistic human development. The Prophet’s evaluative practices demonstrate a balanced approach, combining moral guidance, intellectual assessment, and behavioral observation. Evaluation, therefore, is not merely a tool for measuring outcomes but also a process of nurturing ethical character and spiritual awareness. This study contributes to the academic discourse by offering a conceptual framework for Islamic educational evaluation that aligns with both classical teachings and contemporary pedagogical needs. It highlights the relevance of prophetic models in developing a more holistic, value-based evaluation system capable of addressing the complexities of modern education.